Pandangan Al-Ghazali terhadap Ittihad dan Hulul: Al-Ghazali’s View on Ittihad and Hulul - Muniron Muniron (Fenomena, 2006)
The debate over the mystical union between the Sufi and God, particularly the concepts of ittihad and hulul, has long been controversial in Islamic thought and has often been accused of contradicting monotheism. This study aims to examine and describe Al-Ghazali’s position on both doctrines within Sufism. Using a qualitative library research approach, data were collected from Al-Ghazali’s primary works, including Al-Munqidz min ad-Dlalal and Misykat al-Anwar, and analyzed using a hermeneutic method. The findings reveal that Al-Ghazali categorically rejects real (hakiki) ittihad and hulul as impossible, both rationally and theologically, because they violate the fundamental principle of tawhid by blurring the distinction between Creator and creature. However, he accepts and appreciates metaphorical (majazi) ittihad and hulul, considering them a higher form of tawhid, as exemplified by the utterances of Abu Yazid al-Bustami and Mansur al-Hallaj. The study concludes that Al-Ghazali’s seemingly ambiguous stance is resolved by distinguishing between literal and metaphorical union. It is recommended that future research explore the socio-political contexts influencing Sufi doctrinal formulations. Perdebatan tentang penyatuan mistis antara sufi dengan Tuhan, khususnya konsep ittihad dan hulul, telah lama menjadi isu kontroversial dalam pemikiran Islam dan sering dituduh bertentangan dengan monoteisme. Penelitian ini bertujuan untuk mengkaji dan mendeskripsikan pandangan Al-Ghazali terhadap kedua doktrin tersebut dalam tasawuf. Dengan menggunakan pendekatan penelitian kepustakaan kualitatif, data dikumpulkan dari karya-karya primer Al-Ghazali, seperti Al-Munqidz min ad-Dlalal dan Misykat al-Anwar, serta dianalisis dengan metode hermeneutika. Hasil penelitian menunjukkan bahwa Al-Ghazali secara tegas menolak ittihad dan hulul hakiki sebagai hal yang mustahil secara rasional dan teologis, karena melanggar prinsip dasar tauhid dengan mengaburkan batasan antara Pencipta dan makhluk. Sebaliknya, ia menerima dan mengapresiasi ittihad dan hulul majazi sebagai bentuk tauhid yang lebih tinggi, sebagaimana dicontohkan oleh ungkapan Abu Yazid al-Bustami dan Mansur al-Hallaj. Penelitian ini menyimpulkan bahwa ambiguitas tampak dalam pandangan Al-Ghazali terselesaikan dengan membedakan penyatuan literal dan metaforis. Disarankan agar penelitian selanjutnya mengeksplorasi konteks sosio-politik yang mempengaruhi formulasi doktrin sufi.